Quality of Life in Children with Congenital Birth Defects (Journal of Rangpur Medical College, 2024)
Background: Congenital birth defects are a leading cause of morbidity and mortality in children, with significant long-term impacts on health and quality of life (QoL). Objective: This study aimed to assess the quality of life (QoL) in children with congenital birth defects in Bangladesh, focusing on the influence of age, type of defect, and surgical interventions. Methods: This prospective cohort study was conducted at the Department of Pediatrics, 250 bedded General Hospital, Nilphamari, Bangladesh from July 2023 to June 2024. A total of 200 children aged 5-18 years with documented congenital anomalies were selected. Data were collected through medical record reviews and structured interviews using the Pediatric Quality of Life Inventory (PedsQL). Statistical analyses, including Chi-square tests and ANOVA, were employed to assess the relationships between QoL scores, age, type of defect, and surgical interventions. Results: The study revealed that the mean PedsQL scores decreased with age, with the lowest scores observed in the 16-18 years age group. Congenital heart defects were the most prevalent, affecting 40% of participants, followed by neural tube defects (20%) and cleft lip/palate (15%). Children with CHDs and neural tube defects had lower QoL scores compared to those with other defects. Additionally, 90% of participants underwent surgical interventions, with multiple surgeries associated with lower QoL. Conclusion: The study highlighted the significant impact of congenital defects on QoL, particularly among older children and those with more severe conditions like CHDs and neural tube defects. These findings underscored the need for targeted interventions to improve the long-term QoL of affected children.J Rang Med Col. September 2024; Vol. 9, No. 2: 21-26